Discrepancies between mechanical and biomechanical measurements of soccer shoe traction on artificial turf - Sterzing, T.; Müller, C.; Schwanitz, S.; Odenwald, S.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study analyzed mechanical and biomechanical traction properties of four different stud configurations on artificial soccer turf. Mechanical traction parameters showed statistical differences between the shoe conditions for the friction coefficient during acceleration and force rates during cutting and turning. Biomechanical force ratios statistically discriminated between the four stud configurations for cutting. It is concluded that stud configurations featuring more studs are better suited for playing on artificial turf compared to more aggressive stud configurations with only a small number of studs. It was shown that a combined approach of mechanical and biomechanical testing procedures is needed for traction testing as results differ. In contrast to mechanical testing biomechanical testing can detect movement adaptation of players.